Estimating Hypoxic Volume in the Chesapeake Bay Using Two Continuously Sampled Oxygen Profiles. Issue 9 (12th September 2018) - Bever, Aaron J.; Friedrichs, Marjorie A. M.; Friedrichs, Carl T.; Scully, Malcolm E.
Abstract: Low levels of dissolved oxygen (DO) occur in many embayments throughout the world and have numerous detrimental effects on biota. Although measurement of in situ DO is straightforward with modern instrumentation, quantifying the volume of water in a given embayment that is hypoxic (hypoxic volume (HV)) is a more difficult task; however, this information is critical for determining whether management efforts to increase DO are having an overall impact. This paper uses output from a three‐dimensional numerical model to demonstrate that HV in Chesapeake Bay can be estimated well with as few as two vertical profiles. In addition, the cumulative hypoxic volume (HVC ; the total amount of hypoxia in a given year) can be calculated with relatively low uncertainty (<10%) if continuous DO data are available from two strategically positioned vertical profiles. This is because HV in the Chesapeake Bay is strongly constrained by the geometry of the embayment. A simple Geometric HV calculation method is presented and numerical model results are used to illustrate that for calculating HVC, the results using two daily‐averaged profiles are typically more accurate than those of the standard method that interpolates bimonthly cruise data. Bimonthly data produce less accurate estimates of HVC because high‐frequency changes in oxygen concentration, for example, due to regional‐weather‐ or storm‐induced changes in wind direction and magnitude, are not resolved. The advantages of supplementing cruise‐based sampling with continuous vertical profiles to estimate HVC should be applicable to other systems where hypoxic water is constrained to a specific area by bathymetry. Plain Language Summary: The Chesapeake Bay supports a diverse range of recreational and commercial fisheries. However, every summer the amount of oxygen dissolved in the bay's bottom water decreases to levels lethal for fish and shellfish, termed a "dead zone." To make informed management decisions and understand the health of the ecosystem, it is important to understand the variability in the dissolved oxygen and the amount of water with low dissolved oxygen. In this study, we used both observations collected from boats and three‐dimensional computer models to demonstrate that the region of low dissolved oxygen is strongly constrained by the geometry of the Chesapeake Bay. Because of this geometric constraint, the amount of low dissolved oxygen water can be accurately calculated if continually monitored with only two vertical profiles. In contrast, the current method uses numerous locations sampled only twice per month. This study demonstrated that continuous vertical profiles at as few as two locations provide a better estimate of the volume of hypoxia in any given year. This means that the amount of hypoxic water can be estimated in real time using an ocean observing system that efficiently supplements the current monitoring program, because only a few continuous monitoring locations are needed. Key Points: Chesapeake Bay hypoxic volume is largely constrained by the bay's geometry and bathymetry Two continuously sampled profile locations yield better estimates of cumulative hypoxic volume than bimonthly data at numerous locations A Geometric hypoxic volume method provides a simple way to calculate hypoxic volume from two continuous vertical oxygen profiles